Nasal septal angle deviation: effect on lateral wall in nasal obstruction - Bagri, Neha; K., Kavirajan; Chandra, Ranjan; Agarwal, Yatish; Gupta, Neetika; Mandal, Shantanu (International Journal of Research in Medical Sciences, 2018)
Background: Deviation of the nasal septum (DNS) refers to the convexity of the septum to one side disturbing the nasal physiology with obstructed nasal breathing leading to lateral nasal wall abnormalities and paranasal sinuses (PNS) mucosal disease. Knowledge of nasal morphological parameters plays an important role in planning successful nasal surgery. Our aim was to evaluate the angle of septal deviation (ASD) on CT scan and study its influence on the lateral nasal wall abnormalities and PNS mucosal disease. Methods: A prospective cross-sectional observational study was conducted on 130 patients with clinical evidence of DNS and chronic sinusitis. The direction and severity of DNS was recorded on CT scan along with evaluation of lateral nasal wall and sinus mucosal abnormalities. Results: Increasing ASD had statistically significant correlation with the lateral nasal wall abnormalities, most commonly, contralateral middle and inferior turbinate hypertrophy (p-value <0.0001). No significant association was found with the incidence of ipsilateral or contralateral osteomeatal complex (OMC) obstruction and sinus mucosal disease. Conclusions: The direction and severity of septal deviation has significant impact on contralateral middle and inferior turbinate hypertrophy. The analysis of these ancillary pathologies can be of great help to the surgeon in better management of patients with nasal obstruction.